Enhancing income of sugarcane farmers in subtropical India: Potential technologies - Chandra, Amaresh; Jain, Radha; Roy, M M (Indian Farming, 2020)
A supply chain in sugarcane sector based on bud chip based planting material and wide scale adoption of available technologies in minimizing post-harvest sucrose losses will open up newer avenues for enhancing farmers’ income. Such an effort will complement the on-going efforts on promotion of desirable superior varieties and other agronomical packages.